Southeast view of the Grotto, now the Goldsmith's Arms - Maddocks; Schnebbelie, Robert Blemmell (Tufts Archival Research Center, 2008)
In the Parish of St. George, Southwark. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 2.